Times of mobility : transnational literature and gender in translation - Lukić, Jasmina; Forrester, Sibelan E. S. (Sibelan Elizabeth S.); Faragó, Borbála (Transnational perspectives in gender studies., 2019)
"In an era of increased mobility and globalization, a fast growing body of writing originates from authors who live in-between languages and cultures. In response to this challenge, transnational perspective offers a new approach to the growing body of cultural texts with an emphasis on experiences of migration, transculturation, bilingualism, and (cultural) translation. The introductory analysis and the fifteen essays in this collection critically interrogate complex relations between transnational and translation studies, bringing to this dialogue a much needed gender perspective. Divided into three parts (From Transnational to Translational; Reading Across Borders and Transnational in Translation), they address a range of issues relevant for this debate, from theoretical problems to practical questions of literary criticism and translation, understood as an act of cultural interpretation. The volume mostly deals with contemporary literary and cultural production, but also with classical texts and modernist literature. Its particular quality is a strong (although not exclusive) focus on Central and East European literatures, and more generally on women writers. Its interdisciplinary, transnational, and intercultural perspective makes it relevant across disciplinary boundaries, from literary and translation studies to gender studies, cultural studies, and migration studies"--